Cardiovascular Disease Prevention in Adolescents: eHealth, Co-Creation, and Advocacy - Raeside, Rebecca (Med Sci (Basel), 2019)
Cardiovascular disease (CVD) is the leading cause of death globally. Early atherosclerotic changes can begin to occur early in life and though adolescence. The prevalence of modifiable CVD risk factors, namely, smoking, poor diet quality, excessive alcohol intake, physical inactivity, and overweight and obesity can exacerbate the early onset of atherosclerosis. There is a need to improve modifiable risk factors during adolescence to prevent progression to CVD in later life. Electronic health (eHealth) behaviour change interventions are a potential solution for adolescents to improve CVD risk factors, given adolescents are digital frontrunners and digital technology is wide-reaching. The process of co-creating eHealth behaviour change interventions with adolescents is a promising strategy to improve intervention effectiveness and engagement. Additionally, effective youth advocacy is an emerging strategy for CVD prevention in adolescents. This narrative review evaluates published eHealth behaviour change interventions targeting cardiovascular disease risk factors in adolescents, which utilize a co-creation process, describe the emerging role of advocacy in CVD prevention for adolescents and provide recommendations for future interventions.